Y-chromosome haplogroup I prehistoric gene flow in Europe - Rootsi, Siiri (Documenta Praehistorica, 2006)
To investigate which aspects of contemporary human Y-chromosome variation in Europe are characteristic of primary colonization, late-glacial expansions from refuge areas, Neolithic dispersals or more recent events in gene flow haplogroup I was analyzed. The analysis of Hg I Y chromosomes revealed several sub-clades with distinct geographic distributions. Sub-clade I1a accounts for most of Hg I in Scandinavia, with a rapidly decreasing frequencytowards the East European Plain and the Atlantic fringe; but microsatellite diversity reveals that the Iberian Peninsula/Southern France refugial area could be the source region of the early spread of both I1a and the less common I1c. I1b* extends from the eastern Adriatic to Eastern Europe, and declines noticeably towards the southern Balkans, and abruptly towards North Italy. This clade probably diffused after the Last Glacial Maximum from a homeland in the Balkans or Eastern Europe. In contrast, I1b2 most probably arose in southern France/Iberia, underwent a post-glacial expansion, and marked the human colonization of Sardinia about 9000 years ago.
Keywords: Europe; Evropa; archaeology; arheologija; prazgodovina; neolitik; človek; genetics; genetika; poselitev; human migration; migracije